Odpowiedź :
Odpowiedź:
a)
5x-8=6-2x
5x+2x=8+6
7x=14/:7
x=2
b)
-3-2x=3(x+4)
-3-2x=3x+12
-15=5x/:5
x= -3
c)
16-(5-3x)=2(2x-1)+6(x-6)
16-5+3x=4x-2+6x-36
11+38=7x
7x=49/:7
x=7
d)
1-x=2x+2/3/×3
3-3x=2x+2
-5x=-1/:-5
x=1/5
e)
2x+1/1-2x=2/3
2x+1=2/3(1-2x)
2x+1=2/3-4/3x
2 4/3x= -1/3/×3/10
x= -0,1
Szczegółowe wyjaśnienie:
Odpowiedź:
a)
5x - 8 = 6 - 2x
5x + 2x = 6 + 8
7x = 14 / :7
x = 2
b)
-3 - 2x = 3(x+4)
-3 - 2x = 3x + 12
-2x - 3x = 12 + 3
-5x = 15 /:(-5)
x = -3
c)
16 - (5-3x) = 2(2x-1) + 6(x-6)
16 - 5 + 3x = 4x - 2 + 6x - 36
11 + 3x = 10x - 38
3x - 10x = -38 - 11
-7x = - 49 / :(-7)
x = 7
d)
1 - x = [tex]\frac{2x + 2}{3}[/tex] / ·3
3 - 3x = 2x + 2
-3x - 2x = 2 - 3
-5x = -1 /:(-5)
x = [tex]\frac{1}{5}[/tex]
e)
[tex]\frac{2x + 1}{1 - 2x} = \frac{2}{3}[/tex]
3(2x + 1) = 2(1 - 2x)
6x + 3 = 2 - 4x
6x + 4x = 2 - 3
10x = -1 /:10
x = [tex]-\frac{1}{10}[/tex]